El The phantom and dialectic in O mel e as vespas, by Fernando Évora - Rojas Chavez, Roman Manuel (2021)
Fernando Évora’s novel, O mel e as vespas (2015), tells the story of characters related to the origin, development and end of Cancino, a fictional space located in the Portuguese highlands. The progressof this small town and that of the central state, the capital, is not uniform; for this reason, the interaction of both generates conflicts that lead to the destruction of Cancino as a habitable space. The degenerative process of the place is sustained in irreconcilable dialectical relations and manifests its milestones with phantasmagorical appearances. Therefore, this work is divided into two parts. The first section, entitled “Relaciones dialécticas”, deals with the struggle of opposites manifested in Évora’s novel, which is notorious from the conception of the work; likewise, the main points of conflict structured in the narration are addressed. The second section, entitled “Las manifestaciones del fantasma”, focuses on the moments, forms and meanings that spectral presences will have throughout O mel e as vespas. Faced with the absence of critical works on this novel and, in sum, on the literary production by Fernando Évora, thisstudy makes a critical interpretation that ranges from the general, the structure of the work, to particular, the phantasmagorical appearances.